Upaya Peningkatan Prestasi Belajar Pratata Rambut melalui Metode Problem Based Learning pada Mata Pelajaran Pengeritingan Rambut Sanggul Tradisional dan Kreatif - Utami, Tri Puji (Universitas Muhammadiyah Magelang, 2021)
The purpose of this research is to improve learning achievement to hairdressing in curling hair with a roll set in traditional and creative bun curling lessons. This research design uses classroom action research with the Kemmis and Taggart model. This research was conducted at SMK Negeri 3 Magelang involving 34 students of class XI Beauty. Methods of data collection using observation, questionnaires, and test. Data analysisused three stages, namely data reduction, data presentation, and data verification. The result showed that students learning outcomes, motivation, and skills increased in each cycle.